THE INFLUENCE OF LOW-TEMPERATURE PLASMA TREATMENT ON MICROBIAL CONTAMINATION LEVEL OF MEDICINAL PLANT RAW MATERIAL - O. M. Tikhomirova; E. Y. Zagorulko; A. A. Eruzin; M. G. Ozhigova; M. M. Sychev (Разработка и регистрация лекарственных средств, 2019)
Efficacy of non-equilibrium low-temperature plasma treatment for reducing microbial contamination of medicinal plant raw materials (chamomile flowers and peppermint leaves) was studied. Decontamination of plant raw materials was carried out at experimentally defined conditions: exposure time - 5.0 min, glow discharge frequency - 1.76 MHz, working pressure - 0.1 Pa, working gas of plasma - argon. It was found that spore-forming bacteria count after treatment under these conditions decreases by 2 orders of magnitude, yeast and mould count decreases by 3 orders of magnitude.